Strontium, nickel, cadmium, and lead substitution into calcite, studied by density functional theory - Andersson, M P (Langmuir : the ACS journal of surfaces and colloids, 2014)
We have used density functional theory to predict the ion exchange energies for divalent cations Ni(2+), Sr(2+), Cd(2+), and Pb(2+) into a calcite {10.4} surface in equilibrium with water. Exchange energies were calculated for substitution into the topmost surface layer, at the mineral-fluid interface, and into the second layer of the solid. This information can be used as an indicator for cation substitution in the bulk phase, such as for the uptake of toxic metals from the environment and the growth of secondary phases. In both the surface and in the second layer, Ni(2+), Cd(2+), and Pb(2+) substitute exothermically and Sr(2+) substitutes endothermically. Our results agree with published experimental data that demonstrate trace metal coprecipitation with calcite as a sink for Ni(2+), Cd(2+), and Pb(2+), whereas Sr(2+) has a distribution constant significantly smaller than 1. Ni(2+) substitution is favored at the mineral-fluid interface compared with bulk substitution, which also agrees with experimental data. Our results predict that Ni(2+), Cd(2+), and Pb(2+) form a stable solid solution with calcite. Successful prediction of the experimental results gives us confidence in our ability to predict the divalent cation preference for surfaces rather than for sites within the bulk crystal structure, which cannot be directly derived from experiment